Triglyceride Levels and Risk of Type 2 Diabetes Mellitus: A Longitudinal Large Study. Issue 2 (January 2016) - Beshara, Amani; Cohen, Eytan; Goldberg, Elad; Lilos, Pearl; Garty, Moshe; Krause, Ilan
The relationship between triglyceridemia and diabetes mellitus remains unclear. This study evaluated the risk of diabetes and impaired fasting glucose associated with a wide range of triglyceride levels. A longitudinal retrospective study was carried out employing data from a screening center between the years 2000 and 2012. Inclusion criteria were absence of diabetes at baseline and attendance at the center at least twice over a 5-year period. Participants were divided by fasting blood glucose level (normal/impaired) at the first visit. A total of 5085 participants were eligible for the study. Of the 4164 normoglycemic participants at baseline, 40 (0.96%) had diabetes and 998 (24%) had impaired fasting glucose by the end of the study. On stepwise logistic regression analysis, every 10 mg/dL increase in triglyceride level significantly increased the risk of diabetes by 4% and of impaired fasting glucose by 2% (p<0.001). This association held true even when rising triglyceride levels remained within the accepted normal range (<150 mg/dL, p<0.001). Sustained increments in serum triglyceride level, even within the accepted normal range, are an independent risk factor for diabetes mellitus and impaired fasting glucose in normoglycemic participants.